ORAL CORRECTIVE FEEDBACK: ERROR TYPES, AND STUDENTS’ UPTAKE IN EFL CLASSROOM - Lailatus Sa’adah (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2021)
Corrective feedback has become a big issue among second and foreign language researchers. Its effectiveness while being implemented in the class is still the subject of debate. Moreover, its impact on second and foreign language learners’ performance is also a topic of discussion. Most researches claimed that corrective feedback has a positive effect on EFL learners. Therefore, this paper seeks information about the implementation of corrective feedback, the error types and students’ uptake found in the class. For this purpose, interviews and observations were used to collect data from a teacher and tenth grade students of senior high school in one of city in central java. The findings showed that there are three types of oral corrective feedback found in the class, they are; explicit correction, metalinguistic, and clarification request. Moreover, the students are frequently do a phonological error and semantic error while speaking. In regard to the students’ uptake, acknowledgement, repetition, off-target, and peer-repair are mostly found from the teacher and students interaction.